High Efficiency Solar Cell Panel - Liikala, Richard (My University, 1976)
Solar Cells of at least 10% conversion efficiency were fabricated from silicon wafers of one inch diameter and the same processing procedure was applied to wafers of three inch diameter. Four of the three inch diameter solar cells were affixed to a galvanized steel plate and hooked in a parallel configuration to make a solar cell panel. A piece of special plastic was placed over the solar cells on the panel and hermetically sealed to protect the solar cells from the environment which in time would degrade the performance of the solar cells.
Keywords: efficiency; solar cell panel; silicon wafers